Results from a blind comparison of chloride measurements by accredited laboratories and the implications for enforcing increasingly stringent HCl emission limits in EU legislation. (3rd April 2022) - Coleman, Marc D.; Ellison, Matthew; Robinson, Rod; Smith, Thomas O.M.
ABSTRACT: We report results from a blind comparison of six analytical laboratories ISO/IEC 17025 accredited for the implementation of the analytical element of EN 1911, which involves the quantification of chloride in deionized water collected from HCl emitting industrial processes regulated under the EU's Industrial Emissions Directive (IED). Both "synthetic" (sodium chloride dissolved in deionized water) and "real" (extracted and collected from a stack simulator facility) samples were prepared across ranges which were equivalent to concentrations in the stack of 0–10 mg·m −3 and 0–60 mg·m −3, respectively. Laboratory measurements of the real samples showed significantly poorer performance than the synthetic, implying that the use of synthetic samples in national proficiency testing schemes may be leading to an overly optimistic view of the uncertainties that can routinely be achieved in measurements of real industrial processes. In addition, at the applicable emission limits (10 mg·m −3 and 3 mg·m −3 ) and measurement ranges (0–15 mg·m −3 and 0–4.5 mg·m −3 ) under the IED and more recent BAT Conclusions legislation it was found that of the real samples 22 out of 102 (21.6%) and 28 out of 51 (54.9%), respectively, of the measurements would not comply with the overall uncertainty that at least one national regulator considers as necessary for EN 1911 to be an "effective tool" for the calibration of automated measuring systems (AMSs – process plant operator analyzers providing continuous monitoring of emissions). Hence, it is proposed that at the next revision of EN 1911 the standard should be revised to give the same degree of consideration to the analytical element of the method as the sampling element. Key analytical laboratory uncertainty sources should be identified, numerical uncertainty requirements should be placed on key analytical uncertainty sources, and there should be an overall uncertainty requirement for the analytical element. Implications: The deviations observed between laboratories ISO/IEC 17025 accredited for chloride analysis bring into question the ability of the current version of EN 1911 (the CEN Standard Reference Method for monitoring HCl industrial emissions) to meet the uncertainty requirements associated with emission limits under both the EU's Industrial Emissions Directive and the increasingly stringent industrial sub-sectors BAT Conclusions legislation. It is proposed that at the next revision of EN 1911 that uncertainty guidance and requirements for the analytical element are added if this measurement method is to continue to be mandated across Europe for ensuring emissions data meet legislative quality requirements.